Inovasi Pembelajaran Pendidikan Agama Islam dalam Era Industri 4.0 - Harimawan Harimawan; Arif Budi Rahardjo; Eko Harianto (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
The development of Industry 4.0 is a challenge for the world of education, including Islamic religious education (PAI) learning. Teachers are required to be able to face more complex challenges. There are many complexities in the challenges of the industrial revolution 4.0 in the field of PAI learning. This research aims to find out about Islamic religious education learning innovations in industry 4.0 at SMK Muhammadiyah 1 Bantul. This research uses qualitative research methods which are delivered descriptively. PAI learning innovation is applied with the term